Exploring Caspase-independent Apoptosis Mechanism Of New -carboline Derivatives In Chronic Myelogenous Leukemia - Nageswararao, Meroshine (2025)
Cancer is known as one of the serious causes of mortality among the world population. One of the most reliable treatments for cancer is chemotherapy, though drug resistance and severe side effects have caused major setbacks to effective treatment. Lately, it has been found that understanding the mechanism of action of a chemotherapy agent might lead to a more effective treatment for this disease which is named as targeted therapy. In the constant search for new anticancer agent alternatives, β-carboline alkaloids have been identified as good candidates for a new chemotherapy drug. β-carboline compounds M25, M56 and M62 were synthesised, and their purities were confirmed using gas chromatography-mass spectrometry (GC-MS) analysis. Cytotoxicity of the compounds were evaluated using MTT assay against K562 human CML cell line as well as non-cancer cells Hs27 human foreskin cell line and BALB/c3T3 mouse fibroblasts cell line. The IC50 values for K562 were 0.8μM, 0.78μM and 0.123μM for M25, M56 and M62 respectively, and their selectivity index (SI) values were reported to be in the range of 2.9 and 42.53 for both non-cancer cell lines. In addition, apoptosis analysis was conducted using flow cytometry and all three compounds induced apoptosis as a mode of cell death on K562 cell line.